Kajian persepsi komuniti tempatan terhadap pelancongan sukan: Monsoon Cup, Pulau Duyung - Mohd Azmin, Nurul Azhani (2008)
In Terengganu, the development and promotion of sporting events is becoming increasingly popular, due in part to the role of sport in building the nation’s identity, the economic benefits, and a growing awareness of the importance of health and fitness within the community. Given this increased popularity it is important that the impacts of these events upon the local ‘host’ communities be understood. Social impacts have been given more and more attention in recent years by event researchers, due to the recognition that the long term sustainability of such events can only be achieved with the approval and participation of residents. This research addresses these issues in the context of Pulau Duyung, Kuala Terengganu using the case of Monsoon Cup Events. This thesis adopts a Qualitative method approach using interviews and observation. The findings confirm that it is vital to investigate and understand impacts of events on host communities. The findings are also consistent with theories identified in the literature in terms of the nature of social impacts on host communities. The overall results indicate that residents are aware of both the positive and negative impacts of Monsoon Cup Events. Respondents highlight positive impacts such as economic benefits, exposure of Pulau Duyung and increase community pride. The involvement of local community in this event are very passive and its have been effected to the host perceptions. Most of the major development is not given any benefit to the locals.